The diversity of the Brazilian regional Audit Courts on government auditing - André Feliciano Lino; André Carlos Busanelli de Aquino (Revista Contabilidade & Finanças, 2017)
ABSTRACT Currently, the 33 regional audit courts are responsible to monitor the public financial management cycle for states and municipalities and to judge the compliance of governors’ acts to the laws regarding procurement and civil servants’ employment from more than 20,000 governmental entities under their jurisdiction. This article aims to analyze the diversity of internal configuration of these regional audit courts and to discuss the potential associations with the financial auditing quality their teams usually run. We conducted interviews with external auditors and IT directors from 18 courts, followed by triangulation to official documents from the audit courts, such as audit manuals and activities reports. The audit quality drivers were identified within the governmental auditing literature, supporting the evidences collected by the interviews content analysis. Despite all regional auditing bodies in Brazil were based on the Napoleonic model, the analysis indicates the identified configurations vary according to the team’s organization and size, auditor rotation and use of data reporting systems. The discussion shows that dissimilarities on the courts’ configurations, as they are responsible to audit a specific country area, will contribute to a different coercion level on fiscal and accounting issues to state and municipalities, due a combination of characteristics which could mitigate or improve the audit quality. This paper additionally suggests some precautions, based on the organization alignment literature, for the use of proxies to control audit quality effects in the public finance studies in Brazil.